El nacimiento del estado moderno y los orígenes de la economía política - Míguez, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2009)
This article analyzes the origin of Political Economy both as a parallel phenomenon and conditioned by the consolidation of national states. Economy, on the one hand, and Political Science, on the other, currently propose an apparent dichotomy between economic and political spheres. In spite of that, both disciplines had common interests in their origins. This work sets out two objectives: on the one hand, to analyze the theoretical proposals on the origins of Modern States; on the other hand, to identify the connections between these origins and the rise of Political Economy in the period of transition from feudalism to Capitalism in Western Europe. This is done by raking in the fundamental aspects of the canonical texts of both disciplines.